Optimal time of administration of fentanyl in reducing hemodynamic response in endotracheal intubation - Guntur Muhammad Taqwin; Gusti Ngurah Artika; Sri Rahardjo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2014)
Laryngoscopy and endotracheal intubations are frequently conducted in general anesthesia.However, it can stimulate symphatic and sympatoadrenal activities. Several non andpharmacological interventions have been used to reduce the symphatic stimulation. Fentanyl isone of the opioid drugs that frequently used to decrease the cardiovascular responses after theintubations. In order to obtain an optimal effect, fentanyl should be administered in appropriatetime. This study was conducted to compare the time of fentanyl administration at 2, 5 and 7minutes before endotracheal intubation to reduce hemodynamic responses. This was anobervational study with a prospective cohort design on patients who were going to undergoelective sugical using general anesthesia followed laryngoscopy intubation in Dr Sardjito GeneralHospital and met the inclusion and exclusion criteria. The patients were then divided into 3groups i.e patients who received fentanyl 1.5 μg/kg body weight (BW) intravenously (IV) 2minutes (Group A), 5 minutes (Group B) and 7 minutes (Group C) before laryngoscopy intubations.The hemodynmic responses including sistolic and diastolic blood pressure (SBP and DBP), meanarterial pressure (MAP), heart rate (HR) and rate pressure product (RPP) were monitored andrecorded every 1 minute during 7 minutes period. The result showed that fentanyl administration5 minutes before laryngeal intubation was more effective in the decrease hemodynamic responsethat those 2 and 7 minutes. Significantly different in SBP in 2, 3, 4 and 7 minutes observationswas observed (p<0.05). Furthermore, significantly different in MAP in 2, 3 and 4 minutesobservation and in RPP in 1, 2, 3, 4 and 7 minute observation were also observed (p<0.05). Nosignificantly different was observed in HR during observation (p>0.05). In conclusion, theadministration of fentanyl 1.5 μg/kg BW IV at 5 minutes before intubation is more effectiveagainst hemodynamic responses in endotracheal intubation.